Differential Modulation of GABAA and NMDA Receptors by an α7-nicotinic Acetylcholine Receptor Agonist in Chronic Glaucoma - Zhou, Xujiao; Zong, Yuan; Zhang, Rong; Zhang, Xuejin; Zhang, Shenghai; Wu, Jihong; Sun, Xinghuai (Frontiers in Molecular Neuroscience, 2017)
Presynaptic modulation of γ-aminobutyric acid (GABA) release by an alpha7 nicotinic acetylcholine receptor (α7-nAChR) agonist promotes retinal ganglion cell (RGC) survival and function, as suggested by a previous study on a chronic glaucomatous model from our laboratory. However, the role of excitatory and inhibitory amino acid receptors and their interaction with α7-nAChR in physiological and glaucomatous events remains unknown. In this study, we investigated GABAA and N-methyl-D-aspartate (NMDA) receptor NR2B subunit activity in control and glaucomatous retinal slices and the regulation of amino acid receptor expression and function by α7-nAChR. Whole-cell patch-clamp recordings from RGCs revealed that the α7-nAChR specific agonist PNU-282987 enhanced the amplitude of currents elicited by GABA and reduced the amplitude of currents elicited by NMDA. Pretreatment with the α7-nAChR antagonist methyllycaconitine (MLA) blocked the PNU-282987-induced positive modulation of the GABAA receptor and the negative modulation of the NMDA receptor. The frequency and the amplitude of glutamate receptor-mediated miniature glutamatergic excitatory postsynaptic currents (mEPSCs) were not significantly different between the control and glaucomatous RGCs. Additionally, PNU-282987–treated slices showed no alteration in the frequency or amplitude of mEPSCs relative to control RGCs. Moreover, we showed that expression of the α1 subunit of the GABAA receptor was downregulated and the expression of the NMDA receptor (NMDAR) NR2B subunit was upregulated by ocular hypertension, and these effects of elevated intraocular pressure (IOP) were also prevented by PNU-282987. In conclusion, retina GABAA and NMDARs are modulated positively and negatively, respectively, by activation of α7-nAChR in in vivo chronic glaucomatous models.